Rail Transportation 2006
DOI: 10.1115/imece2006-14420
|View full text |Cite
|
Sign up to set email alerts
|

Train-to-Train Impact Test of Crash Energy Management Passenger Rail Equipment: Occupant Experiments

Abstract: As part of an ongoing passenger rail crashworthiness effort, a full-scale impact test of a train with crash energy management (CEM) passenger cars was conducted on March 23, 2006. In this test, a train made up of a CEM cab car, four CEM coach cars, and a locomotive impacted a stationary train of similar mass at 30.8 mph. This test included five occupant experiments on the cab car and the first coach car to evaluate occupant injury risk and seat/table performance during the collision using anthropomorphic devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…See Table 1 for a list of injury results. For more detailed information on the design of the FRA prototype table and the test results, see the sources listed in [10] and [6], respectively. Having demonstrated the effectiveness of a workstation table designed to absorb energy during a collision, the next step is developing an industry standard that can be used to establish a minimum level of crashworthiness for workstation tables.…”
Section: Figure 1 Schematic Of Fra Prototype Tablementioning
confidence: 99%
“…See Table 1 for a list of injury results. For more detailed information on the design of the FRA prototype table and the test results, see the sources listed in [10] and [6], respectively. Having demonstrated the effectiveness of a workstation table designed to absorb energy during a collision, the next step is developing an industry standard that can be used to establish a minimum level of crashworthiness for workstation tables.…”
Section: Figure 1 Schematic Of Fra Prototype Tablementioning
confidence: 99%
“…FRA tested the prototype table in a full scale train-to-train test with two ATDs with specialized abdominal regions, the Test Device for Human Occupant Restraint (THOR) ATD and the Hybrid III Railway Safety ATD [3]. The tests demonstrated that an energy absorbing workstation table provides improved safety to the passenger in an incident.…”
Section: Introductionmentioning
confidence: 99%
“…These criteria will be developed through a combination of previously-conducted full-scale testing of a prototype design using advances ATDs capable of measuring upper abdominal response, and through a sensitivity analysis carried out using computational techniques. A multi-body model including the THOR ATD was developed in MADYMO and refined based on full-scale test results [3]. This model can be used to predict the upper abdominal injury risk to occupants in a simulated sled test environment using varying table edge force-crush characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The 8G crash pulse is specified in the existing American Public Transportation Association (APTA) Standard for Rowto-Row Seating in Commuter Rail Cars [1] and in the Federal Code of Regulations 49 CFR 238.233 [2], and represents nominal collision conditions. The 12G crash pulse represents the collision environment measured in the cab car during a previous full-scale train-to-train impact test of passenger rail cars incorporating crash energy management [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The prototype commuter seat was initially tested in rearfacing and forward-facing occupant experiments during the train-to-train test of CEM equipment in March 2006 [4]. It was anticipated that large reaction forces would occur at the seat attachment points.…”
Section: Introductionmentioning
confidence: 99%